2017
DOI: 10.1063/1.5001286
|View full text |Cite
|
Sign up to set email alerts
|

Propagation characteristics of audible noise generated by single corona source under positive DC voltage

Abstract: The directivity and lateral profile of corona-generated audible noise (AN) from a single corona source are measured through experiments carried out in the semi-anechoic laboratory. The experimental results show that the waveform of corona-generated AN consists of a series of random sound pressure pulses whose pulse amplitudes decrease with the increase of measurement distance. A single corona source can be regarded as a non-directional AN source, and the A-weighted SPL (sound pressure level) decreases 6 dB(A) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…The relative humidity of the measurement environment was maintained at 40%-60%, and the ambient temperature was maintained between 20 °C and 30 °C. Studies have shown that temperature and humidity changes in this small range have little effect on the characteristics of negative corona discharge [10,18], therefore, in this work, the influences of temperature and humidity on the experimental results are ignored and the effect of altitude is mainly considered.…”
Section: Experimental Site and Environmentmentioning
confidence: 99%
“…The relative humidity of the measurement environment was maintained at 40%-60%, and the ambient temperature was maintained between 20 °C and 30 °C. Studies have shown that temperature and humidity changes in this small range have little effect on the characteristics of negative corona discharge [10,18], therefore, in this work, the influences of temperature and humidity on the experimental results are ignored and the effect of altitude is mainly considered.…”
Section: Experimental Site and Environmentmentioning
confidence: 99%
“…In recent years, researchers have gradually focused on the time domain characteristics of the corona discharge, further revealing the process of corona discharge generated audible noise. North China Electric Power University and Tsinghua University have studied the time domain characteristics of DC corona audible noise and obtained the single noise-pulse waveform generated by positive and negative corona discharge [47][48][49][50], as shown in Figure 3. North China Electric Power University studied the sound wave that generates from corona discharge and the typical waveform, as shown in Figure 3 [45].…”
Section: Characteristicsmentioning
confidence: 99%
“…In Figure 4, the red waveform, black waveform and blue arrows are the noise, current and the indicator arrows, respectively. The existing research results show that DC corona current and audible noise have the following correlation characteristics [47,48], as shown in Figure 4:…”
Section: Characteristicsmentioning
confidence: 99%
“…Ref. [24] gives the equivalent A-weight sound level and 8 kHz sound pressure level of the conductor in the corona cage in Beijing (50 m above sea level), and the…”
Section: Spectral Characteristics Of Audible Noisementioning
confidence: 99%